El Physiologus como fuente gráfico-textual de la emblemática animalística de la Edad Moderna - José Julio García Arranz (Janus: Estudios sobre el Siglo de Oro, 2014)
The Physiologus, a collection of Christian allegories drawn from the natural properties attributed to certain animals and plants, real or fantastic, composed in Greek language somewhere in the Eastern Mediterranean -Alexandria or Syria- between the second and fourth centuries of our era, has generated a vast literature since the late 19th century around its origin, authorship and versions in different languages. However, except for a few honorable exceptions, had not yet been addressed in depth the influence that this booklet was able to exert on the literary-visual genre of books of emblems from the 16th century on. Usually considered by critics as major source of the bookish Emblematics animalistic side, in this paper we aim to address in detail the true impact of the Physiologus reached both in pictures and allegorical interpretations of the emblems which, a priori, seem to keep some kind of thematic relationship with the primitive Christian text.